Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1088/0741-3335/51/12/124045
|View full text |Cite
|
Sign up to set email alerts
|

Miniaturized non-thermal atmospheric pressure plasma jet—characterization of self-organized regimes

Abstract: The study reports for the first time on self-organization effects in a radio frequency (RF) plasma generated with a miniaturized non-thermal atmospheric pressure plasma jet. The source is configured as a capacitively coupled RF jet (27.2 MHz) with two outer ring electrodes around a quartz capillary (d = 4.0 mm) between which a gas mixture flows at typical rates of 0.05-5 slm. The application background of this source is the deposition of thin films with a PECVD process. Therefore, thin film producing agents ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
47
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 25 publications
1
47
1
Order By: Relevance
“…The accuracy of the TTMS flow rates given in Table 1 is estimated as 10%. The RF power (27.12 MHz, DTG2710, Dressler) supplied to the plasma was 6 or 15 W. This, along with the given flow ensures a source operation in a distinctive discharge mode with four azimuthally rotating discharge filaments dubbed Locked Mode 4 (LM4) and described in detail in [23]. Here, the time needed to deposit a film is longer: 15 min for one experiment.…”
Section: Radiofrequency Jetmentioning
confidence: 99%
“…The accuracy of the TTMS flow rates given in Table 1 is estimated as 10%. The RF power (27.12 MHz, DTG2710, Dressler) supplied to the plasma was 6 or 15 W. This, along with the given flow ensures a source operation in a distinctive discharge mode with four azimuthally rotating discharge filaments dubbed Locked Mode 4 (LM4) and described in detail in [23]. Here, the time needed to deposit a film is longer: 15 min for one experiment.…”
Section: Radiofrequency Jetmentioning
confidence: 99%
“…The systematic overview of distinguished regimes has been published in Ref. 25. The filamentary structure of the plasma jet represents a common attribute of this kind of discharges.…”
Section: Experimental Set-upmentioning
confidence: 99%
“…25 The discharge regime of the plasma source is suitable for the task because of a symmetric patterning and regular steady dynamics of the filaments. Plasma parameters and conditions of this jet have been already characterized in a recently published study, 7 which presents a comparative base for the results of laser schlieren deflectometry (LSD) analysis.…”
Section: Introductionmentioning
confidence: 99%
“…1(a) and (c) shows that at certain instants the discharge is still filamentary. The filaments tend to wind around the inner wall of the capillary, which is typical for locked modes described in [2] and [3]. Vice versa, Fig.…”
mentioning
confidence: 69%
“…This problem can be overcome by adding molecular admixture, which promotes diffusive, non-contracted character of the plasma. Recently [2], [3], it was found that filamentary nature, typical for the argon jet, can be easily affected by small variations in experimental conditions, namely power and gas flow. In this way, the plasma inhomogeneity can be partly compensated by an optimization of temporal delocalization of the filament(s).…”
mentioning
confidence: 99%